Outcomes of Diabetic Toe Amputation With Versus Without Metatarsal Head Resection for Single Ray Wet Gangrene: A Preliminary Study - Kaissar Yammine; Mohammad Honeine; Joseph Mouawad; Ghadi Abou Orm; Youssef Jamaleddine; Chahine Assi (Journal of Foot and Ankle Research, 2025)
ABSTRACT Background Diabetic wet gangrene of the toes is a serious condition that puts at risk the limb and life of patients. Two types of amputation are used when infection is around the metatarsophalangeal joint (MTPJ): complete toe disarticulation and toe amputation including metatarsal head resection. Because very few published papers analyzed the results of toe amputation for wet gangrene, our study aimed to evaluate the outcomes of both techniques. Methods This is a retrospective comparative study of highly selective patients admitted for a single toe/ray diabetic wet gangrene that were treated with toe amputation through MTPJ (TA‐MTPJ) versus toe amputation with resection of the metatarsal head (TA‐MHR). Three primary outcomes were set for analysis: healing rate and the frequencies of infection recurrence and additional surgeries, including reamputations. Results The sample included 31 cases: 12 cases (39%) with TA‐MTPJ and 19 cases (61%) with TA‐MHR. Outcomes of TA‐MTPJ versus TA‐MHR were as follows: (a) healing frequency 66.7% versus 58% (p = 0.6), (b) infection recurrence 50% versus 52.6% (p = 0.8), (c) osteomyelitis 41.6% versus 42.1% (p = 0.8), and (d) reamputation 33.3% versus 47.3% (p = 0.4). Conclusions This study showed high complications after toe amputation for diabetic digital wet gangrene, with a trend for higher frequency of complications after TA‐MHR compared to TA‐MTPJ. For any type of amputation required for toe wet gangrene, it is likely that a more proximal level of index amputation is required.